Non-Invasive Method to Estimate Red Blood Cell in Blood. - Quiñonez, Yadira; Almeraya, Said; Almeraya, Selin; Reyna, Jorge; Mejía, Jezreel (Journal of Medical Systems, 2019)
This work proposes a non-invasive method to estimate the number of red blood cells in the blood. To achieve the development of this research, first, a photosensitive device was designed, which is formed by a phototransistor with a transparent casing allowing the red light coming from a red LED to penetrate the sensor. This means, that when the intensity of the light varies, the amount of current flowing through the sensor also changes. In consequence, this variation in electric current causes a variation on the voltage drop across the connections of a resistor, which is read by a microcontroller that calculates the number of red blood cells. Second, some formulas were established to represent the relationship between the extreme points of a data set obtained during a sampling process. Finally, to verify the device operation, a sampling process was performed in volunteer patients (range 18–84 years) with venous blood samples run on a laboratory hematology analyzer, a total 68 measurements were made to people of different ages and genders, of which 34 are females and 34 are males.